Cover Picture: (Prop., Explos., Pyrotech. 3/2016). Issue 3 (June 2016) - Unknown
Abstract : The cover picture shows: Mastering Insensitive Munitions is a Multidisciplinary Challenge. This frontispiece is a collage of the topics of 16 technical papers that cover a range from Ab‐Initio Design of Energetic Materials to the Understanding of the Response of Munitions to Individual Stimuli.